1999
DOI: 10.1366/0003702991946659
|View full text |Cite
|
Sign up to set email alerts
|

Spatially and Temporally Resolved Absorption Studies of YO in the Plume of Laser-Ablated Y2O3

Abstract: A spatially and temporally resolved transient absorption technique has been employed to investigate the dynamics of ground-state YO during 355 nm laser ablation of Y2O3. Time-of-flight (TOF) measurements of the expanding YO plume in vacuum and in Ar or O2 ambient are reported. During the initial expansion of YO in vacuum, the center-of-mass velocity and the expansion velocity increase with distance up to the boundary of the Knudsen layer. In the presence of oxygen, reactions of the ablated atomic species with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We analyzed the kinetics of excited and lower levels populations of a selected Al atomic transition at various distances from the target by combining the OES and LAS. The temporal distribution of a species in the plume at a certain distance from the target surface, commonly referred to as timeof-flight (TOF) emission [32][33][34] or absorption signal 35,36 provides information about the persistence of the chosen species in the plume and the peak arrival/delay time at the selected spatial position and hence the expansion velocity. For performing the spatial analysis of lower-level population, time-resolved probe transmission was recorded at various distances from the target surface when the probe laser was fixed at the peak of the Al I transition at λ 0 = 394.4 nm.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the kinetics of excited and lower levels populations of a selected Al atomic transition at various distances from the target by combining the OES and LAS. The temporal distribution of a species in the plume at a certain distance from the target surface, commonly referred to as timeof-flight (TOF) emission [32][33][34] or absorption signal 35,36 provides information about the persistence of the chosen species in the plume and the peak arrival/delay time at the selected spatial position and hence the expansion velocity. For performing the spatial analysis of lower-level population, time-resolved probe transmission was recorded at various distances from the target surface when the probe laser was fixed at the peak of the Al I transition at λ 0 = 394.4 nm.…”
Section: Resultsmentioning
confidence: 99%
“…26,28 The leading edge of m aterial is known to initially travel at supersonic speeds, with velocities ranging from 2 to 20 km/s. 24,29,30 Although measurem ents have shown that this initial velocity drops rapidly to subsonic speeds, a conservative estimated average speed of 1 km /s will m ove the leading edge of m aterial 1 cm in 10 m s. However, it has been shown that a lower concentration distribution of material will trail the bulk distribution by up to several milliseconds. 26 This consideration leads to the following scenario: Setting the laser delay at 2 m s will result in the leading edge of ablated material passing through the plasma interaction region 200 to 300 m s before the discharge metastable Ar population maximizes in the interaction region.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is in agreem ent with previous results for laser ablation in an argon atmosphere, in which the quantity of ablated material reaching an obser vation region displays an exponential decay with increasing distance and pressure. 29 This nding is a result of increased scattering of the m aterial by the Ar ll gas for greater pathlengths and higher pressure. For observations at higher pressure, the spatial distribution should decay faster with distance than at lower pressures.…”
Section: Resultsmentioning
confidence: 99%
“…58,60 The leading edge of material is known to initially travel at supersonic speeds, with velocities ranging from 2 to 20 km/sec. 56,61,62 Although measurements have shown that this initial velocity drops rapidly to subsonic speeds, a conservative estimated average speed of 1 km/sec will move the leading edge of material 1 cm in 10 µs. However, it has been shown that a lower concentration distribution of material will trail the bulk distribution by up to several milliseconds.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with previous results for laser ablation in an argon atmosphere, in which the quantity of ablated material reaching the observation region displays an exponential decay with increasing distance and pressure. 61 This is a result of increased scattering of the material by the Ar fill gas for greater pathlengths and higher pressure. For observations at higher pressure the spatial distribution should decay faster with distance than at lower pressures.…”
Section: Resultsmentioning
confidence: 99%